2010
DOI: 10.1007/s11266-010-9146-4
|View full text |Cite
|
Sign up to set email alerts
|

From Cowboys to Diplomats: Challenges for Social Entrepreneurship in The Netherlands

Abstract: Social entrepreneurship-a new business model that combines a social goal with a business mentality-is in a transitional phase, from a rough cowboy market to a more established market niche. This process results in two interconnected dilemmas for the social entrepreneur. First, how it can capture market share despite its role as an antagonist to current market values. Second, how it can prevent the loss of its own core values in the course of greater interaction with the incumbent regimes. Using a tool known fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 14 publications
0
18
1
Order By: Relevance
“…Thus, although the correlations show that women have a greater tendency toward the social orientation in projects than men, as argued in previous studies by Cukier et al (), Van Ryzin et al () and Witkamp et al (), we have found that the impact is not statistically significant, and so our first hypothesis is not supported.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Thus, although the correlations show that women have a greater tendency toward the social orientation in projects than men, as argued in previous studies by Cukier et al (), Van Ryzin et al () and Witkamp et al (), we have found that the impact is not statistically significant, and so our first hypothesis is not supported.…”
Section: Discussioncontrasting
confidence: 59%
“…We have found more evidence as regards sex. Although the literature makes it clear that men have more general entrepreneurial attitude than women (Espíritu and Sastre ), most studies find that women tend more to social projects than men (Cukier et al ; Van Ryzin et al ; Witkamp et al ); therefore, as the first working hypothesis we posit that:
Hypothesis 1. Women show greater social orientation in their projects than men.
…”
Section: Theoretical Backgroundmentioning
confidence: 94%
See 1 more Smart Citation
“…As stated by Witkamp, Royakkers and Raven (2011), the inclusion in the community of the social organization, the experience of the social issues and the strong involvement of the main stakeholders lead to the adoption of a response model that accommodates the characteristics of the target population and of the rural territory where they live. Most of the solutions mentioned above are not radical social innovations but rather derive from the knowledge of the reality of the situation and the combination of pre-existing elements (i.e., incremental innovation).…”
Section: -Conclusionmentioning
confidence: 99%
“…internal communal social capital (networking with a wide range of community groups) and external collaborative social capital (networking with partners from private and public sectors). With regard to the latter, the relationships with government are argued to be significant for success (Witkamp, Royakkers, and Raven 2011). Sharir and Lerner (2006) and Marshall (2011) insist on the importance of building and using networks, especially through long-term cooperation relationships, for the social venture's success.…”
Section: A Critical Skill Of Social Entrepreneurs and A Fundamental Amentioning
confidence: 99%